Optimalisasi Lembaga Pengelola Zakat Infaq Shadaqah (ZIS) Melalui Pendampingan Penguatan Manajemen dan Program Kerja Lembaga Amil Zakat - Yaqin, Ainul; Suadi; Justsinta Sindi Alivi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This Community Service (PkM) project is based on the low effectiveness of zakat, infaq, and sadaqah (ZIS) fund management by LAZISNU (Nahdlatul Ulama’s Zakat Institution) in Wonorejo Village, Kunjang District, Kediri Regency. Despite the significant ZIS potential, its management had not been optimized productively. The PkM aimed to strengthen institutional capacity and enhance mustahik empowerment programs through a participatory approach. Methods included field observation, interviews, training on Islamic microenterprise management, program planning assistance, and collaborative evaluation with partners. The results showed improved understanding among LAZISNU administrators regarding productive zakat and the development of locally-based empowerment initiatives. Several mustahik also started microenterprises with guidance from the PkM team. The discussion highlights the importance of synergy between LAZISNU, the community, and academia in building a strategic and sustainable zakat management system. This PkM demonstrates that optimizing LAZISNU’s role contributes not only to economic improvement but also to spiritual awareness and social independence among mustahik.